2012
DOI: 10.1371/journal.pone.0032795
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Type Specific Roles for PTEN in Establishing a Functional Retinal Architecture

Abstract: BackgroundThe retina has a unique three-dimensional architecture, the precise organization of which allows for complete sampling of the visual field. Along the radial or apicobasal axis, retinal neurons and their dendritic and axonal arbors are segregated into layers, while perpendicular to this axis, in the tangential plane, four of the six neuronal types form patterned cellular arrays, or mosaics. Currently, the molecular cues that control retinal cell positioning are not well-understood, especially those th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
56
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(61 citation statements)
references
References 68 publications
5
56
0
Order By: Relevance
“…By contrast, PI3K/Akt signaling is an important 'hub' in the network of pathways required for the formation of MGPCs in the zebrafish retina (Wan et al, 2014). During development of the mammalian retina, loss of function of PTEN, leading to gains in PI3K/Akt signaling, disrupts the mosaic patterning and dendritic morphogenesis of inner retinal neurons, whereas cell proliferation and cell fate are unaffected (Sakagami et al, 2012;Cantrup et al, 2012). Collectively, these findings indicate context-and speciesspecific functions of PI3K/Akt and mTor signaling in developing and regenerating retina.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, PI3K/Akt signaling is an important 'hub' in the network of pathways required for the formation of MGPCs in the zebrafish retina (Wan et al, 2014). During development of the mammalian retina, loss of function of PTEN, leading to gains in PI3K/Akt signaling, disrupts the mosaic patterning and dendritic morphogenesis of inner retinal neurons, whereas cell proliferation and cell fate are unaffected (Sakagami et al, 2012;Cantrup et al, 2012). Collectively, these findings indicate context-and speciesspecific functions of PI3K/Akt and mTor signaling in developing and regenerating retina.…”
Section: Discussionmentioning
confidence: 99%
“…Pax-6-Cre-mediated deletion results in accelerated neurogenesis and premature loss of retinal progenitor cells accompanied by tissue hypertrophy not attributed to excessive stem cell production (Cantrup et al, 2012). This is in contrast to observations from other neuronal progenitor populations (see below) and illustrates the importance of spatio-temporal context in determining the cellular consequence to PTEN loss.…”
Section: Cell Proliferation/cell Fatementioning
confidence: 99%
“…Recent studies in Zebrafish have shown the role of transcription factor Irx7 in regulating retinal lamination by affecting neurite outgrowth [38]. Another factor namely PTEN phosphatase also mediates the mosaic spacing, fasciculation, and dendritic arborization of TH amacrine cells and of horizontal cells, likely in a Dscam/Sema-independent manner [39]. Although we currently understand the role of these signaling molecules in IPL development, we are yet to assimilate the full network of molecules upstream and downstream of the signaling factors that play into this regulation.…”
Section: Introductionmentioning
confidence: 99%